The Role of Waqf in Advancing Quality Education and Community Empowerment in Alignment with the Sustainable Development Goals - Palasenda , Nabil Fikri; Salikurrahman, Muhammad (el-Tarbawi, 2024)
Initially, waqf in Indonesia was managed individually without clear regulations. Over time, the need to regulate waqf management emerged to ensure its effective administration and targeted utilization. One significant effort in this regard is leveraging waqf to support the development and empowerment of educational quality, aligning with the Sustainable Development Goal (SDG) of Quality Education. Islamic boarding schools (pesantren) play a crucial role in realizing this objective. This study adopts a qualitative approach through literature analysis and library research, utilizing data from books, academic journals, and relevant documents. Through a comprehensive literature review, this research examines the role of waqf and its implications for enhancing educational quality. The findings indicate that waqf has a significant impact on the development of quality education, particularly within pesantren. The utilization of waqf in these educational institutions not only provides financial support for infrastructure and facilities but also fosters the development of educational programs, scholarships, and teacher training, which enhance the overall quality of education. Furthermore, waqf in pesantren contributes to the empowerment of local communities by providing accessible and affordable education. The implications of these findings suggest that the integration of waqf into educational systems can be a sustainable and effective means to improve educational outcomes and help achieve SDG 4. Therefore, policymakers and educational stakeholders should consider strengthening waqf management frameworks to maximize its potential in supporting quality education, particularly in underserved regions.